Which Factors Play a Crucial Role in the Toilet Training Process? - Dewi, Vivian Nanny Lia (Universitas Aisyah Pringsewu, 2024)
The prolonged use of diapers can cause skin problems in babies due to inflammation in the diaper-covered area. Toilet training is a crucial milestone in a child's development, marking the transition from diaper to toilet use. This study aims to identify the factors associated with toilet training in toddlers. It is a quantitative study with a cross-sectional approach conducted in October 2023. Eighty respondents (40 mothers and 40 toddlers) were involved using a total sampling technique. The independent variables in this study were the mother's factors (age, education, and knowledge) and the child’s factors (age and gender). The dependent variable was the child's readiness for toilet training. Data were collected using surveys and questionnaires and then analyzed using the Chi-Square test. The results show that the factors significantly associated with toilet training readiness are maternal knowledge (p=0.003, OR 0.60 CI 95% (0.264–5.208)) and the child's age (p=0.002, OR 0.374 CI 95% (0.257-5.680)). The research recommendation is for mothers to start teaching their children toilet training between the ages of 2 and 3.